The feasibility of tropical pitcher plant (Nepenthes sp.) exploration booklet as a learning media - Syaiful Azhar; Melfa Aisyah Hutasuhut (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2022)
Learning media is designed to arouse curiosity and increase students' knowledge. If only listening to verbal information from the teacher, students are more likely to ignore what is being taught. Therefore, the use of learning media has proven to be effective. Currently, learning materials are sourced from textbooks. This study aims to determine the feasibility, practicality, and effectiveness of a booklet developed from the inventory of pitcher plants (Nepenthes sp.) as a learning medium for high school/MA students. The research stages include the needs analysis stage, the booklet planning stage, the booklet creation stage, the validation stage, the trial stage, and the multiplication of booklet prints. The research instruments are in the form of validation sheets and questionnaires. Material experts and design experts assess validation. The practical tests of students and teachers include evaluating the booklet's physical appearance and overall content. The validation assessment was 88.6% and 90.4% "very valid" by design and material experts, respectively. The product's practicality based on the responses of students and teachers obtained a result of 96.7%, and the product's effectiveness got a result of 94% with the category of "excellent." This data shows Indonesia's biodiversity is a force that can be developed to meet the opportunities and challenges in education.Abstrak Media pembelajaran dirancang untuk membangkitkan rasa ingin tahu serta menambah ilmu pengetahuan siswa. Jika hanya mendengarkan informasi verbal dari guru, siswa lebih cenderung mengabaikan apa yang diajarkan. Oleh karena itu, penggunaan media pembelajaran terbukti efektif. Saat ini, materi pembelajaran bersumber pada buku teks. Penelitian ini bertujuan untuk mengetahui kelayakan, kepraktisan dan keefektifan buklet yang dikembangkan dari inventarisasi tumbuhan kantong semar (Nepenthes sp.) sebagai media pembelajaran bagi siswa SMA/MA. Tahapan penelitian yang dilakukan meliputi tahap analisis kebutuhan, tahap perencanaan buklet, tahap pembuatan buklet, tahap validasi, tahap uji coba, dan perbanyakan cetakan buklet. Instrumen penelitian berupa lembar validasi dan kuesioner. Validasi dinilai oleh ahli material, ahli desain. Uji praktis oleh respon siswa dan wawancara guru dalam menilai penampilan fisik dan keseluruhan isi buklet. Penilaian validasi yang diperoleh sebesar 88,6%, 90,4% “sangat valid” masing-masing oleh ahli desain dan ahli material. Kepraktisan produk berdasarkan respon siswa dan guru memperoleh hasil 96,7%, dan keefektifan produk memperoleh hasil 94% dengan kategori “sangat baik”. Data ini menunjukkan keanekaragaman hayati di Indonesia adalah kekuatan yang dapat dikembangkan untuk menghadapi peluang dan tantangan dalam pendidikan.